4n+9=3

Simple and best practice solution for 4n+9=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n+9=3 equation:


Simplifying
4n + 9 = 3

Reorder the terms:
9 + 4n = 3

Solving
9 + 4n = 3

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 4n = 3 + -9

Combine like terms: 9 + -9 = 0
0 + 4n = 3 + -9
4n = 3 + -9

Combine like terms: 3 + -9 = -6
4n = -6

Divide each side by '4'.
n = -1.5

Simplifying
n = -1.5

See similar equations:

| 3(5-x)=18 | | 4(x-3)=-24 | | 5c+7=28 | | 14-2(3p+1)=6(4+p) | | 2(x+1)-5(x-3)=5 | | -2y-3y+8=8-5y-12 | | (-7)(-6)= | | 1356=2t-284 | | -39-(-23)= | | 6x-5=3x-29 | | 6x-16=-10 | | 5x=9+2x | | 9x+23=-4 | | 3-4x=-9 | | 9(z-1)-2(3z+4)=7 | | 12x-6=11x | | -6+(-6)-(-5)+7= | | -4(-6-6)= | | 10-(2x-4)+3x=16 | | (-2+4)*-49-3= | | 2*-49-3= | | 2x-49-3= | | -36-9= | | 8x-(3x+10)=15 | | .5x-3=1.5x+4 | | 18=(x*7)+.5(7*0.3) | | 46-75= | | 2+x=-6 | | x+2=0 | | 17u-12+20u+36= | | x-1.5=-1.5 | | 5=8+x |

Equations solver categories